Dissecting Causal Relationship Among Immune Cells, Plasma Metabolites and Coronary Atherosclerosis: A Mendelian Randomization Study - Cao Q; Liu J; Sun J; Qian S; Song J; Zheng H; Wen J; Zheng B (ImmunoTargets and Therapy, 2025)
Qi Cao, Jiajing Liu, Jingyu Sun, Shuangshuang Qian, Junhuai Song, Haoyang Zheng, Jinkun Wen, Bin Zheng Department of Biochemistry and Molecular Biology, Key Laboratory of Neural and Vascular Biology, Ministry of Education, Hebei Medical University, Shijiazhuang, 050017, People’s Republic of ChinaCorrespondence: Bin Zheng; Jinkun Wen, Department of Biochemistry and Molecular Biology, Key Laboratory of Neural and Vascular Biology, Ministry of Education, Hebei Medical University, No. 361 Zhongshan East Road, Shijiazhuang, 050017, People’s Republic of China, Email doublezb@hebmu.edu.cn; wjk@hebmu.edu.cnBackground: Circulating immune cells and metabolites are linked to coronary atherosclerosis, but the specific causal relationships and the role of metabolites as mediators remain unclear.Methods: Summary statistics from GWAS datasets on immune cells (n=3,757), circulating metabolites (n=8,299), and coronary atherosclerosis (cases n=51,589; controls n=343,079) were analyzed using bidirectional Mendelian randomization. Two-step and multivariate Mendelian randomization were employed to identify mediating metabolites, with inverse variance weighting (IVW) as the primary method.Results: We identified nine immune cell phenotypes, including specific T-cell and monocyte populations, with significant causal links to coronary atherosclerosis. Additionally, 41 plasma metabolites across four metabolic pathways were identified, including 3-hydroxy-2-ethylpropionate and trans-2-hexenoylglycine. Mediation analysis revealed that 3-hydroxy-2-ethylpropionate mediated the effect of IgD+ CD24+ B-cells on coronary atherosclerosis (mediating effect: 0.961; 95% CI: 0.955– 0.967), while trans-2-hexenoylglycine regulated IgD+ CD24+ B-cells, showing a mediation ratio of 16.7% (mediating effect: 0.983; 95% CI: 0.981– 0.986).Conclusion: Key immune cell phenotypes and plasma metabolites were linked to coronary atherosclerosis. The roles of 3-hydroxy-2-ethylpropionate and trans-2-hexenoylglycine in regulating B-cell function suggest potential therapeutic targets for prevention and treatment. Keywords: immune cells, coronary atherosclerosis, plasma metabolites, Mendelian randomization, B-cell function